Кримінально-правова охорона суспільної моралі в Україні: антропологічний вимір - Бойченко, Віталій Петрович; Бойченко, Виталий Петрович; Boychenko, Vitaliy P. (My University, 2021)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.08 – кримінальне право та кримінологія; кримінально-виконавче право. – Національний університет «Одеська юридична академія», Одеса, 2021. Дисертація є першим у вітчизняній науці кримінального права спеціальним комплексним дослідженням антропологічних основ кримінально-правової політики забезпечення безпеки суспільної моралі в сучасній юридичній доктрині та кримінальному законодавстві України. На підставі цього розроблено основні перспективи кримінально-правової охорони суспільної моралі в Україні в умовах транзиції до нового законодавства з урахуванням новітніх змін, пов’язаних із охороною прав дітей. Під кримінально-правовою охороною розуміють заходи по забезпеченню безпеки існуючих суспільних відносин та інтересів та утримання громадян від злочинних посягань шляхом визначення в кримінальному законі шкідливих для особи, суспільства та держави правопорушень та встановлення за їх вчинення кримінальних покарань та інших заходів кримінально-правового впливу. Основною гіпотезою дослідження є констатація можливості використання суб’єктних характеристик діяльності індивіда та толерантності її оцінки у інформаційному суспільстві в якості основи криміналізації діянь проти суспільної моралі. Не тільки суспільна небезпека, але й мережева дозволеність та підтримка індивідуальних девіацій робить можливою визнання діяння суспільно-небезпечним. Отже, матеріальна ознака злочину (небезпека для держави та суспільства) детермінується значущістю недозволених практик для особистості (соціальної групи) та підкріплюється толерантністю до порушення даних норм у референтній групі (субкультурі), чи у соціумі у цілому. В роботі підтримується наукова позиція стосовно того, що удосконалення правових механізмів регулювання суспільних відносин, що виникають у духовній сфері, повинно стати пріоритетним напрямком державної політики (у тому числі і кримінальної політики) в галузі забезпечення моральної і духовної безпеки особистості, суспільства і держави. Здійснення такої політики припускає, зокрема, і вдосконалення існуючої системи і юридичних ознак складів відповідних злочинів, а також розробку нових складів злочинів (з урахуванням специфіки як кримінальної відповідальності, так і духовної сфери життя) і включення відповідних правових норм у чинний КК України. Для досягнення цього в роботі здійснено теоретико-методологічний аналіз наукових досліджень стану використання сучасного антропологічного підходу до кримінально-правових явищ; удосконалено методологію антропологічного дослідження кримінальних правопорушень; визначено методологічні засади дослідження антропологічних алгоритмів і технологій формалізації кримінального права; ідентифіковано природу кримінальних правопорушень проти суспільної моралі та моральності, у яких суспільна мораль є основним безпосереднім або додатковим безпосереднім об’єктом посягання; визначено особливості антропологічних характеристик генези криміналізації діянь проти суспільної моралі та моральності та напрямки її охорони; охарактеризовано злочини та покарання, кримінальні правопорушення проти суспільної моралі як особливу сферу використання антропологічної методології права; розкрито зміст, природу і призначення сучасної кримінально-правової політики в аспекті антропологічного розуміння та моделювання правопорушень проти суспільної моралі; окреслено основні перспективи вдосконалення кримінального законодавства у сфері, що вивчається.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.08 – уголовное право и криминология; уголовно-исполнительное право. – Национальный университет «Одесская юридическая академия», Одесса, 2021. Диссертация является первым в отечественной науке уголовного права специальным комплексным исследованием антропологических основ уголовно-правовой политики обеспечения безопасности общественной нравственности в современной юридической доктрине и уголовном законодательстве Украины. На основании этого разработаны основные перспективы уголовно-правовой охраны общественной морали в Украине в условиях транзиции к новому законодательству с учетом новейших изменений, связанных с охраной прав детей. Под уголовно-правовой охраной понимают меры по обеспечению безопасности существующих общественных отношений и интересов и содержания граждан от преступных посягательств путем определения в уголовном законе вредных для личности, общества и государства правонарушений и установления за их совершение уголовных наказаний и иных мер уголовно-правового воздействия. Основной гипотезой исследования является констатация возможности использования субъектных характеристик деятельности индивида и толерантности, ее оценки в информационном обществе в качестве основы криминализации деяний против общественной морали. Не только общественная опасность, но и сетевая дозволенность и поддержка индивидуальных девиаций делает возможной признание деяния общественно опасным. Итак, материальный признак преступления (опасность для государства и общества) детерминируется значимостью запрещенных практик для личности (социальной группы) и подкрепляется толерантностью к нарушению данных норм в референтной группе (субкультуре) или в социуме в целом. В работе поддерживается научная позиция о том, что совершенствование механизмов регулирования общественных отношений, возникающих в духовной сфере, должно стать приоритетным направлением государственной политики (в том числе и уголовной политики) в области обеспечения моральной и духовной безопасности личности, общества и государства. Осуществление такой политики предполагает, в частности, и совершенствование существующей системы и юридических признаков составов соответствующих преступлений, а также разработку новых составов преступлений (с учетом специфики как уголовной ответственности, так и духовной сферы жизни) и включение соответствующих правовых норм в действующий УК Украины. Для достижения этого в работе осуществлен теоретико-методологический анализ научных исследований состояния использования современного антропологического подхода к уголовно-правовых явлений; усовершенствована методология антропологического исследования уголовных правонарушений; определены методологические основы исследования антропологических алгоритмов и технологий формализации уголовного права; идентифицировано природу уголовных преступлений против общественной морали и нравственности, в которых общественная мораль является основным непосредственным или дополнительным непосредственным объектом посягательства; определены особенности антропологических характеристик генезиса криминализации деяний против общественной морали и нравственности и направления ее охраны; охарактеризованы преступления и наказания, уголовные правонарушения против общественной морали как особый объект антропологической методологии права; раскрыто содержание, природа и назначение современной уголовно-правовой политики в аспекте антропологического понимания и моделирования правонарушений против общественной морали; обозначены основные перспективы совершенствования уголовного законодательства в сфере изучаемого языка.

Thеsіs fоr а Cаndіdаtе Dеgrее іn Lаw іn spеcіаlty 12.00.08 – Crіmіnаl Lаw аnd Crіmіnоlоgy; Crіmіnаl Enfоrcеmеnt Lаw. – Nаtіоnаl Unіvеrsіty "Оdеssа Lаw Аcаdеmy", Оdеssа, 2021. The dissertation is the first special comprehensive study of the anthropological foundations of criminal law policy to ensure the security of morals in modern legal doctrine and criminal law of Ukraine in the domestic criminal law. Based on the concept of criminal law protection of public morals in Ukraine in the transition to the new legislation was developed. The study of criminal law protection of public morals as a socially and historically determined phenomenon of anthropogenesis is a complex process to study the social preconditions for criminalization of such crimes, features of the modern concept of criminal law protection and prospects for improving the relevant norms. Morals in the criminal law sense is a social relationship that is formed and developed in society, to ensure respect for some people to others, shyness, respect for universal values established in society, non-compliance with which a person leads to public condemnation and affects the level of cultural and spiritual development of her as a person. Under criminal law protection are measures to ensure the security of existing social relations and interests and deter citizens from criminal encroachments by defining in criminal law harmful to the individual, society and the state offenses and establishing criminal penalties and other measures of criminal law influence. The paper supports the scientific position that the improvement of mechanisms for regulating public relations arising in the spiritual sphere should become a priority of public policy (including criminal policy) in the field of moral and spiritual security of the individual, society and the state. The implementation of such a policy involves, in particular, improving the existing system and legal features of the crimes, as well as the development of new crimes (taking into account the specifics of both criminal responsibility and spiritual life) and the inclusion of relevant legal norms in the current Criminal Code of Ukraine. Thus, the policy in the field of combating this type of crime is a system of political and legal measures aimed at reducing the level and dynamics of criminal offenses by all political, economic measures and legal means (punishment, other criminal measures, measures to treat offenders), taking into account on the main characteristics of the development of society and moral values in it. Criminal protection of public morals and individual morality is an important element in the development of the modern rule of law. Moral prohibitions on negative actions condemned by society are primary in determining what is punishable, but the logic of social development shows a certain inconsistency of modern criminal laws. The state must punish the duty for the sake of social peace, but this duty is leveled by a whole bunch of restrictions and balances of executive and legislative power. the criminal law norm is not conditioned by social needs and internal necessity, which leads to a conflict between the public consciousness (or the attitudes of individuals) and criminal law prohibitions, leads to mass anomie, genocide, legal nihilism. The anthropological dimension of crimes against public morals requires modern researchers to focus not only on the issue of dogmatic analysis of the norm (purely criminal law approach) or axiological assessment of the existence and existence of the norm (criminological or sociological approach), but also integrative dynamic analysis of the essence and existence concerning various participants of criminal legal relations. The structure of the policy of ensuring the security of relations of public morals and morality as an object of criminal law protection includes: 1) security (preservation) of historical and cultural heritage as a set of the most important material carriers of spirituality, which is the result of organizational, legal and other measures aimed at preventing the destruction, destruction or damage of cultural property, their illegal circulation in the form of illegal transfer of ownership; 2) security of the moral foundations of society as a system of protection against the destruction of the national mentality of the Ukrainian people in the form of the moral foundations of the nation, traditions and customs based on them, ideas of justice, goodness and equality, etc.; 3) religious security of the individual and society as a state of political and legal protection and social stability of religious relations, including freedom of conscience and religion, non-interference of the state and anyone in church affairs, inadmissibility of spreading destructive cults in Ukraine, totalitarian sects, etc. To determine this, the work carried out a theoretical and methodological analysis of scientific research on the state of use of a modern anthropological approach to criminal law phenomena. The methodology of anthropological research of criminal offenses has been improved; the methodological foundations of the study of anthropological algorithms and technologies for the formalization of criminal law have been determined. The nature of criminal offenses against public morals and morality in which public morals is the main direct or additional direct object of encroachment were identified. The features of the anthropological characteristics of the genesis of the criminalization of acts against public morality and morality and the direction of its protection have been determined. Crimes and punishments, criminal offenses against public morals through the prism of anthropological methodology of law have been іdentified. The content, nature and purpose of modern criminal law policy in the aspect of anthropological understanding and counteraction to offenses against public morality and the main prospects for improving the criminal legislation in the field of the studied phenomenon were outlined.
дис. ... канд. юрид. наук: 12.00.08
Бойченко В.П. Кримінально-правова охорона суспільної моралі в Україні: антропологічний вимір: дис. ... канд. юрид. наук: 12.00.08 / Бойченко Віталій Петрович. Одеса, 2021. 235 с.
Keywords: суспільна мораль; суспільна небезпека діяння та правопорушника; антропологічний метод; кримінальна антропологія; злочини проти суспільної моралі та моральності; кримінально-правова охорона; кримінальна політика; общественная опасность деяния и правонарушителя; антропологический метод; уголовная антропология; преступления против общественной морали и нравственности; уголовная политика; уголовно-правовая охрана; общественная мораль; social danger of the act and the offender; anthropological method; criminal anthropology; crimes against public morals and morality; criminal policy; criminal law protection; public morality